Influence Incentive Green Taxation and Literacy Tax to Green Innovation and Compliance Tax MSMEs in Makassar City - Budiandriani, Budiandriani; Rahmah, Ridhan; Rosyadah, Khairina; Nurnajamuddin, Mahfud (Amkop Management Accounting Review (AMAR), 2025)
This study aims to analyze the influence of green tax incentives and tax literacy on green innovation and tax compliance among MSMEs (Micro, Small, and Medium Enterprises) in Makassar City, with green innovation acting as a mediating variable. The research is motivated by the growing need for MSMEs to transition toward sustainable business practices amidst climate change pressures and fiscal policy demands. Employing an explanatory quantitative approach, the study utilizes Structural Equation Modeling (SEM) with AMOS version 24. A total of 150 active MSMEs were selected through purposive sampling. The findings reveal that both green tax incentives and tax literacy significantly influence green innovation, and green innovation significantly influences tax compliance. Tax literacy also has a direct positive effect on tax compliance, while the direct effect of tax incentives on tax compliance is not significant. However, both green tax incentives and tax literacy indirectly affect tax compliance through green innovation. These results highlight the crucial role of green innovation as a behavioral bridge linking fiscal policy and tax compliance in the MSME sector. The study contributes to theoretical development in sustainable fiscal behavior models and offers practical insights for policymakers and MSME support institutions at the local level.